Determining Poverty Vulnerabilities in Dhaka City Corporation Area: An Asset-based Fuzzy Logic Analysis. Issue 1 (2nd January 2019) - Ullah, Kazi Masel
ABSTRACT: This article presents a list of vulnerability indicators in context of Dhaka city using asset-based approach and evaluates relative vulnerabilities of households using fuzzy logic. Literature review and stakeholder consultation were made to identify vulnerability indicators; and Cheli and Lemmi's distribution function method was mainly applied for fuzzy poverty analysis. Result shows that 16% of the sample households are highly poor, 54% are poor, 24% are moderately poor, and 6% are nonpoor. The study tried to explain the major characteristics of being highly poor, poor, moderately poor, as well as nonpoor.